A New Role of OmpR in Acid and Osmotic Stress in Salmonella and E. coli - Chakraborty, Smarajit; Kenney, Linda J. (Frontiers in Microbiology, 2018)
Bacteria survive and respond to diverse environmental conditions and during infection inside the host by systematic regulation of stress response genes. E. coli and S. Typhimurium can undergo large changes in intracellular osmolality (up to 1.8 Osmol/kg) and can tolerate cytoplasmic acidification to at least pHi 5.6. Recent analyses of single cells challenged a long held view that bacteria respond to extracellular acid stress by rapid acidification followed by a rapid recovery. It is now appreciated that both S. Typhimurium and E. coli maintain an acidic cytoplasm through the actions of the outer membrane protein regulator OmpR via its regulation of distinct signaling pathways. However, a comprehensive comparison of OmpR regulons between S. Typhimurium and E. coli is lacking. In this study, we examined the expression profiles of wild-type and ompR null strains of the intracellular pathogen S. Typhimurium and a commensal E. coli in response to acid and osmotic stress. Herein, we classify distinct OmpR regulons and also identify shared OmpR regulatory pathways between S. Typhimurium and E. coli in response to acid and osmotic stress. Our study establishes OmpR as a key regulator of bacterial virulence, growth and metabolism, in addition to its role in regulating outer membrane proteins.